Exploring the Phenomenon of Foreign Direct Investment: The Impact of Economic Development and Growth Prospects on Location-Specific Advantages in Kosovo. - Kelmendi, Albana (My University, 2023)
The Republic of Kosovo is a landlocked country located in Southeastern Europe. After gaining independence in 2008, Kosovo has been determined to develop a prosperous and sustainable economy. Working to boost foreign direct investment (FDI) in Kosovo in order to accelerate growth in the economy and overall progress has been one of the strategies employed to achieve this goal. The primary objective of this research is to look into how growth and development in the econ-omy prospects influence location-specific advantages sought by foreign companies in Kosovo and to examine how specific market challenges impact the ability of foreign firms to leverage these advantages, using the LSA FDI theory as a theoretical framework. By exploring the factors that impact FDI in Kosovo, this study aims to inform policymakers and stakeholders in developing strategies to promote economic growth and attract foreign investment to the country. The study is based on qualitative research methods, including in-depth interviews with 10 investors operating in various industries and the data collected is analyzed using thematic analysis. The findings suggest that Kosovo offers several location-specific advantages that are attractive to foreign investors, such as a skilled and highly educated workforce, low labor costs, low tax rates, favorable FDI laws, streamlined registration procedures, and strategic location. However, the market challenges that affect the ability of foreign firms to leverage these advantages include corruption, law enforcement issues, perceptions towards regional stability, international recognition, workforce migration, as well as the educational system's quality. The study concludes that Kosovo needs to address these challenges to attract and retain foreign investment, including implementing effective measures to combat corruption, strengthening law enforcement, improving perceptions towards regional stability, increasing international recognition, and addressing workforce migration and education issues. Failure to do so could hinder the country's ability to fully leverage its location-specific advantages and achieve greater sustainable economic growth and development. Lastly, this study adds to the FDI literature by providing important insights into the factors that encourage foreign investment in Kosovo. The study's findings can inform policymakers and stake-holders in developing strategies to promote economic growth and attract foreign investment to Kosovo.
Keywords: Kosovo; foreign investments; international corporations; direct investments; economic growth; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development